Gender Diversity and CEO Profile in Relation to Firm Value in Indonesia: Insights from Dividend Payout Ratio Analysis - Candy Candy; Wendy Wendy; Isnaini Nuzula Agustin (Universitas Muhammadiyah Palembang, 2026)
This study investigates the moderating effect of the dividend payout ratio on the relationship between gender diversity, CEO profile, and firm value. CEO profile is assessed through gender, age, education level, and tenure. The study uses a sample of 130 companies listed on the Indonesia Stock Exchange (IDX) over 2019–2023 period, with secondary data obtained from company websites and the IDX portal. Panel data regression analysis was conducted using EViews 12 to examine the direct effects of gender diversity and CEO characteristics on firm value, as well as the moderating role of the dividend payout ratio. The results reveals that CEO education, profitability, and tenure have a positive and significant effect on firm value, while CEO age and firm size exhibit negative effects. The dividend payout ratio significantly moderates the relationship between gender diversity, CEO characteristics, and firm value, highlighting its strategic importance in corporate governance.